Protein degradation and defense against neurodegenerative disease 1 - Goldberg, Alfred (Henry Stewart Talks, 2014)
Neurodegenerative diseases with inclusion bodies associated with ubiquitin and proteasomes, Abnormal proteins rapidly degraded in cells, The ubiquitin-proteasome pathway, Ubiquitin ligases important in neurological disease, CHIP, Hsp70 and Hsp90, Conditions that induce muscle wasting, Ubiquitin ligases in muscles atrophy, P97/VCP, Autophagy, The Nedd4 ubiquitin-ligase and α-Synuclein, The ESCRT pathway, Proteasomal VS. lysosomal degradation (K48 and K63-linked chains), Expression of Nedd4 in Lewy bodies